Suitability of Populus ciliata (Poplar) for Hardboards - Shukla, K. S.; Shah, R. S.; Bagga, J. K. (Indian Forester, 1985)
Experimental data on the suitability of popular(Populus cilita) for making hardboards is reported. It is observed that it is very suitable species of wood for the purpose. Boards of excellent physical and mechanical properties conforming to the requirement of the specification is 1658-1977' for standard hardboards can be prepared from poplar using a light alkali concentration for cooking the chips in water and giving the boards heat or oil tempering treatment. Addition of sizing agents during board formation stage also gave satisfactory boards.